The ‘Umrānic Thoughts of Ibn Khaldūn and Its Contributions to the Studies of Islamic Sociology and Civilization - Abdul Razak, Abdul Qayuum; Suyurno, S. Salahudin; Nordin, Rawi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
This study discusses the thoughts of ‘umrān by Ibn Khaldūn and its contributions in the sociology and civilization areas. In addition, this study also analyses the ‘umrān philosophy that was first introduced by Ibn Khaldūn in the 14-th century. This study was conducted using the deductive and inductive analysis methodology as well as history-search gathered from the Muqaddimah book and other related past studies. It was found that the ‘umrān theory emphasises on the combination of humans and the nature as well as obedience towards God’s laws, which is seen as the best lifestyle that needs to be practiced by all humankinds. Ibn Khaldūn also emphasised on the aspect where humans should comprehend histories in developing the society in the future. In addition, the ‘umrānic thought is seen as contributing and significance towards the studies of human sociology and civilization. This can be seen when the ideas of ‘umrān have influenced later sociological theories such as Malik Bennabi, Arnold Toynbee and others. In addition, Ibn Khaldūn also established an Islamic sociological framework that included God as the lawmaker, man as generator and nature as the source for utilization. Some scholars also pointed out that Ibn Khaldūn highlighted his ideas on the theory of Muslim revival and the rise and decline of civilization.